Kesurupan dalam Perspektif Psikologi dan Teologi Kristen: Pendekatan Multidisipliner terhadap Pemahaman Penanganan Fenomena Kesurupan - Luke Setyo Anggoro (Fakultas Psikologi Universitas Kristen Satya Wacana, 2025)
ABSTRACT The phenomenon of trance has become an interesting topic for research, especially from a psychological and theological perspective. This research aims to explore the experiences of individuals who have experienced possession, the role of spiritual and psychological intervention, as well as understanding Christian theology regarding this phenomenon. A qualitative approach was used with a phenomenological design, involving 10 participants selected by purposive sampling, including individuals who had experienced possession, their families, priests/clergy and psychologists. Data was collected through in-depth interviews, observations and document studies, then analyzed using thematic analysis. The research results show that trance is understood as a complex phenomenon involving spiritual, psychological and cultural aspects. Spiritual interventions such as deliverance prayers are effective in providing a sense of spiritual relief, while psychological approaches help individuals understand and manage the trance experience from a mental perspective. The Christian theological perspective emphasizes that possession can occur due to spiritual influences that require a holistic approach to recovery. The conclusion of this research is that the phenomenon of trance cannot be fully explained from one point of view alone. The combination of spiritual and psychological interventions has been proven to provide optimal results for individuals who experience them. The implications of this research show the importance of collaboration between religious leaders and mental health practitioners in handling cases of possession, as well as the need for public education to reduce the stigma of this phenomenon. Keywords: Trance, Psychology, Christian Theology